Egypt’s Reservations to the United Nations Convention on the Elimination of Discrimination Against Women and Women’s Rights in Egypt - Necva B. Kazimov (International Institute of Islamic Thought, 2003)
This paper addresses the role that the Convention on the Elimination of Discrimination Against Women (CEDAW) can play to improve women’s conditions and secure their rights in Egypt, in light of that country’s religious-based reservations to the UN convention and its recent constitutional amendment making the Shari`ah its principle source of legislation. Specifically, it addresses Egypt’s reservations to Article 16, which concerns the eradication of discrimination against women in cases of divorce, as this area has been the focus of recent legislative reform. The paper is limited to Egypt, because it is the leading Muslim state in providing women’s rights in the area of family law.